Static, Dynamic and Incremental MAC Combined Approach for Storage Integrity Protection - Fangyong Hou; Hongjun He; Nong Xiao; Fang Liu; Guangjun Zhong (2010 IEEE 10th International Conference on Computer and Information Technology, 2010)
Storage systems are more distributed and more subject to attacks. One basic security requirement is to authenticate the stored data. This paper describes SDI-MAC, a static, dynamic and incremental MAC combined approach to guarantee end-to-end data integrity to clients in distributed data storage environment. SDI-MAC associates two different integrity codes to different granularities of the stored data, applies incremental conversion between the two different kinds of integrity codes, and enhances the ability of MAC based data authentication to resist against replay attack. At last, SDI-MAC can make balance among performance, cost and security. Related approach and system implementation are elaborated, as well as testing results. Theoretical analysis and experimental simulations show that it is a practical and available way to realize data authentication of network storage system.